Economics: macroeconomics - Gushcha, Inna (NUBiP, 2024)
Themes are offered and to the test of question, that allows to check up the knowledge of discipline. A manual is made to order the students of higher educational establishments for independent and interactive preparation.
Рекомендовано навчально-методичною радою факультету аграрного менеджменту НУБіП України
Keywords: економіка; макроекономіка; economics; macroeconomics